Atendimento pré-hospitalar público de Belo Horizonte: uma análise da adoção às medidas de precaução pela equipe multiprofissional. - Maria Henriqueta Rocha Siqueira Paiva (2007)
It was a survey study, accomplished with professionals of the Pre-hospital Attendance Public Service (APh) of Belo Horizonte. The aims were to evaluate the adoption of the precaution measures, through knowledge and attitude; to identify the intervening factors in the adoption of precaution measures; and, to determine the incidence of the work accidents by contact with biological material. The data were collected from June to July of 2006, by a structured questionnaire. For the characterization of the sample, it was performed a descriptive analysis and, to verify the associations, an unvariate analysis through the chi-square test. The multivariate analysis was performed using the logistic regression; it described the relationship among the demographic data, adoption of precaution measures and work accident. The sample studied included 238 professionals (physicians, nurses, nursing technicians/auxiliaries and drivers), 66,8% were male, 51,7% with age inferior to 33 years, 58,4% with time of activity at the APh less than two years, and 69,7% allocated in the Unit of Basic Support. In the analysis of the knowledge, it was observed that the physicians reached an indicator inferior to 75% in relation to precautions standards and destiny of the garbage produced during the pre-hospital service. And, for the drivers, it was observed that the knowledge was considered not appropriate in almost all of the appraised items. In the analysis of attitude, it was observed that none of the professionals reached an index of 75% for use of facial mask and protection glasses, and for indication of the equipment of individual protection. The multivariate logistic regression analysis revealed statistically significant association between drivers and nursing technicians/auxiliaries and the not adoption of precaution measures. The professionals pointed out the need of trainings on occupational risks, basic notions of infection control and the execution of periodic meetings. It was identified an incidence of 20,6% of work accidents involving biological material, 40.8% of these during the handling of sharp edge objects, 49.0% by contact with body fluids and 10.2% by both of them. Among all the injured professionals, the main were physicians (35.3%), followed by nurses (24.0%), nursing technicians/auxiliaries (17.7%) and drivers (16.7%). In broad, the medical evaluation after the accident was not accomplished in 63.3% of the cases, and for 81.6% of these the Communication of Work Accident was not issued. No conduct immediately after the accident was taken in 55.0% of the cases and in 61.2% the serologic attendance was not accomplished. Finally, the multivariate logistic regression evidenced that professionals allocated in the Unit of Advanced Support and activity time more than two years at the APh represented risk factors for the occurrence of work accidents. Due to the results of this study and the social importance of the pre-hospital service it becomes essential to look for strategies in order to improve the professional's knowledge related to the infection control and to the biosafety recommendations, as well as the implantation of a formal program of professional's orientation and attendance after the occurrence of work accidents.